Erotetic arguments from inconsistent premises - Meheus, Joke (Logique et Analyse, 1999)
The aim of this paper is to generalize two basic concepts of Wisniewski's theory of questions, namely question evocation and question generation, to the inconsistent case. For both concepts, I shall present three alternative definitions. Each of these is based on a prioritized adaptive logic. I shall show that, for the consistent case, each of the alternative definitions leads to the same results as the original ones, and that, for inconsistent case, no other changes are introduced than those required for the sensible handling of inconsistencies. I shall also show that, in the generalized case, a new kind of question evocation can be defined (here called stong evocation). I shall demonstrate that if a question is strongly evoked by some inconsistent set of premmises, then each of its direct answers provides guidance on how the inconsistencies should be resolved.